Participatory diagnostic tools under the West African Irrigation Project (WAIPRO) - Gonsalves, Julian Francis (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2013)
The tool is used for identifying the constraints of irrigation systems and implementing appropriate interventions. Water professionals such as irrigation engineers in Burkina Faso and Niger were trained on participatory diagnostic tools through the West African Irrigation Project (WAIPRO).